PENGARUH KONSENTRASI URIN SAPI TERHADAP PERTUMBUHAN SETEK SIRIH MERAH - Juanda, Andreas; Anggorowti, Dini; Sulistyowati, Henny (Jurnal Sains Pertanian Equator, 2019)
This study aims to get the best cow urine concentration for the growth of red betel cuttings. Research has been carried out in Kucipu hamlet, RT 11/06, Capkala village, subdistrictCapkala, Bengkayang district. This research was conducted from March 1 to May 31 2018. The experimental method used was Randomized Block Design (RBD) repeated 3 times and each experiment consisted of 5 plant samples. The variables observed in the study were shoot length, number of leaves, number of roots, number of buds, fresh weight of buds, and root volume. The results showed that the with a of cow urine with a concentration of 200 ml/l was the best concentration for the number of leaves, while for root volume, the number of roots, the number of shoots, dan the length of the shoot, given and not given cow urine showed the same growth. Keywords: Red Betel Cuttings and Cow urine Concentration.